The Evaluation of Regrouping Program in State Elementary Schools - Petronela Merryl Alnet; Bambang Suteng Sulasmono (Jurusan PGMI FTIK IAIN Metro Lampung, 2019)
This study included a qualitative evaluative research evaluation model CIPP (Context, Input, Process, Product) developed by Daniel L Stufflebeam. Data Collection techniques used interviews, Observation and documentation.the result showed In aspect context program, regrouping is needed by school in an effort to imrove the quality of education. In aspect of input program, the planning of regrouping human resources, funds, facilities and the mechanism for implementing the regrouping program is fulfilled and running well. In aspect process, regrouping program of school, not fully implemented according to the objectives of the program. especially in the management of abandoned school buildings, there is a waste of buildings, the school and the Education Office need to be wise and creative in terms of the utilization of the school buildings that are left behind, so that the objectives regrouping of school rcan be fully implemented properly. And aspect product, the implementation regrouping program of the school is fully implemented well, has improved the quality of education in schools, increased student achievement, increased number of students, the use of education funds is more efficient and infrastructure is more effective in terms of use.